Acute Exertional Compartment Syndrome in Young Athletes: A Descriptive Case Series and Review of the Literature. Issue 2 (February 2018) - Livingston, Kristin S.; Meehan, William P.; Hresko, M. Timothy; Matheney, Travis H.; Shore, Benjamin J.
Abstract : Objectives: Acute exertional compartment syndrome (AECS) is a rare presentation of acute compartment syndrome (ACS) after exertion without injury. Unfamiliarity with this entity can lead to delay in diagnosis. The purpose of this study was to increase awareness of AECS and illustrate the morbidities associated with delayed diagnosis. Methods: With institutional review board approval, we conducted a retrospective chart review of all patients who underwent emergent fasciotomies for AECS from 1997–2013 at our institution. Male patients with sports-related closed fractures of the tibia leading to ACS were identified for comparison. Demographic variables, patient-specific factors, treatment, and outcome characteristics were analyzed. Results: Seven male patients (mean age, 17 years) presented to our institution with AECS from 1997–2013, and 9 patients with fracture-related ACS were selected for comparison. All cases of AECS occurred in the leg. In the AECS group, the mean time from symptom onset to diagnosis was 97 hours. Four patients initially had a missed diagnosis. On presentation, 6 of 7 patients experienced neurologic symptoms (motor or sensory deficit), although none had perfusion deficits. The mean compartment pressure was 91 mm Hg. They all underwent isolated anterior and lateral compartment releases (except for 1 patient who required a 4-compartment release) and required a mean of 4 surgeries. The mean follow-up was 270 days. Of the 4 patients with missed diagnoses, 2 had significant neurologic and functional deficits at final follow-up. The other 5 patients had a full recovery. Fracture-related ACS patients were younger, with quicker time from symptom onset to surgery, and required more compartments to be decompressed at surgery. Conclusions: Despite the rarity of AECS, orthopedists as well as primary care, emergency medicine, and sports medicine physicians should maintain a high index of suspicion when examining a patient with leg pain out of proportion to examination after exertion. Delay in diagnosis of AECS is associated with substantial muscle necrosis and morbidity.